2010
DOI: 10.1007/s11920-010-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

New Ways to Classify Bipolar Disorders: Going from Categorical Groups to Symptom Clusters or Dimensions

Abstract: Current psychiatric disorder classifications are based exclusively on categorical models, which were designed to increase the reliability of diagnoses. However, this system has some limitations, and various psychiatric disorders may be classified using a dimensional approach, which is more appropriate when no clear boundaries exist between entities or when examining various features on a continuum. Thus, the forthcoming DSM-5 appears to be undertaking a hybrid approach by including categorical models associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 49 publications
4
29
0
6
Order By: Relevance
“…BD with psychotic features has been suggested to be a subtype of BD [8] with specific personality characteristics; in the prodromal phase, increased energy/goal–directed activity was found more frequently in patients with subsequent psychotic BD than in patients with non-psychotic BD [9]. Psychotic symptoms have been associated with brain dopaminergic activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…BD with psychotic features has been suggested to be a subtype of BD [8] with specific personality characteristics; in the prodromal phase, increased energy/goal–directed activity was found more frequently in patients with subsequent psychotic BD than in patients with non-psychotic BD [9]. Psychotic symptoms have been associated with brain dopaminergic activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on early versus late onset, but recent large multisite studies have identified three potential age at onset‐based subgroups with different clinical presentation, across different cultural settings and birth cohorts : i.e., early onset (mean age at onset ≈ 17 years), intermediate onset (mean age at onset ≈ 26 years), and late onset (mean age at onset ≈ 42 years). The characteristics of the disorder may vary with the age at onset , and those with an early onset appear as a separate subgroup with specific clinical manifestations including higher recurrence rates of mood episodes, more elevated episodes at least in BD‐I , more often depressive onsets , more suicide attempts , higher risk for comorbid borderline personality disorder , higher rates of psychotic symptoms , more frequent neurocognitive impairment , more BD‐I than BD‐II , and more often a family history of BD compared to patients with later onsets.…”
mentioning
confidence: 99%
“…In contrast, if ICD-11 and DSM-V introduce a dimensional diagnostic approach, as suggested by several authors [33,34], adjustment disorder will disappear from the psychiatric nomenclature. As a result, reactions to stressful life events could be described by using psychopathological syndrome scores for dimensions such as depression or anxiety.…”
Section: Discussionmentioning
confidence: 99%